(i) The sum of the first three terms of an arithmetic series is 24 and the sum of the next three terms is -12. Calculate the sum of the first twenty terms of this series.
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
Let's denote the first term of the arithmetic series as \( a \) and the common difference as \( d \). The first three terms of the series are: 1. \( a \) 2. \( a + d \) 3. \( a + 2d \) The sum of the first three terms can be written as: \[ S_3 = a + (a + d) + (a + 2d) = 3a + 3d = 3(a + d) \] According to the problem, this sum is 24: \[ 3(a + d) = 24 \implies a + d = 8 \tag{1} \] The next three terms of the series are: 1. \( a + 3d \) 2. \( a + 4d \) 3. \( a + 5d \) The sum of these three terms can be expressed as: \[ S_3' = (a + 3d) + (a + 4d) + (a + 5d) = 3a + 12d = 3(a + 4d) \] According to the problem, this sum is -12: \[ 3(a + 4d) = -12 \implies a + 4d = -4 \tag{2} \] Now we have two equations: 1. \( a + d = 8 \) 2. \( a + 4d = -4 \) Let's subtract equation (1) from equation (2): \[ (a + 4d) - (a + d) = -4 - 8 \] \[ 3d = -12 \implies d = -4 \] Now substituting \( d \) back into equation (1) to find \( a \): \[ a - 4 = 8 \implies a = 12 \] Thus, we have \( a = 12 \) and \( d = -4 \). Now, we can calculate the sum of the first 20 terms of the series. The formula for the sum of the first \( n \) terms \( S_n \) of an arithmetic series is: \[ S_n = \frac{n}{2} \times (2a + (n-1)d) \] Substituting \( n = 20 \), \( a = 12 \), and \( d = -4 \): \[ S_{20} = \frac{20}{2} \times (2 \cdot 12 + (20 - 1)(-4)) \] \[ = 10 \times (24 + 19 \cdot (-4)) \] \[ = 10 \times (24 - 76) \] \[ = 10 \times (-52) \] \[ = -520 \] Thus, the sum of the first twenty terms of this series is \(\boxed{-520}\).